LOYALITAS KONSUMEN DITINJAU DARI PROMOSI, HARGA, DAN KUALITAS PELAYANAN DI CAFE SINONAMANIS NGANJUK - Hermawan, Robbi Adi; Bhirawa, Sigit Wisnu Setya; Muslih, Basthoumi; Ratnanto, Sigit (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study is to identify and analyze the partial and simultaneous significant effects of promotion, price, and service quality on consumer loyalty at Café Sinonamanis Nganjuk. This study employs a quantitative approach with a causal research design. Data were collected using a closed-ended questionnaire with responses measured on a 1–5 Likert scale, and the instrument was proven to be valid and reliable. The population of this study consists of consumers of Café Sinonamanis Nganjuk who have made purchases. The sampling technique used was purposive sampling, with criteria including having made more than two purchases, residing in Nganjuk, and being at least 17 years of age. The sample size was determined based on Roscoe’s rule of thumb, resulting in a total of 40 respondents. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software. The findings indicate that promotion, price, and service quality have significant partial and simultaneous effects on consumer loyalty at Café Sinonamanis Nganjuk. For future research, it is recommended to employ different research methods, such as qualitative approaches or mixed-method designs, to obtain more in-depth findings. Additionally, the inclusion of other variables is suggested, given that 58.4% of the variance in consumer loyalty may be explained by other independent variables not examined in this study.